A mathematical investigation of equations describing the sediment transport - Chung, Dang Huu (Vietnam Journal of Mechanics, 1990)
In this work the mathematical problem of equations describing the sediment transport was studied. The results show that in the different cases of flow the set of equations has five characteristics, in which two of them are the rates of concentration propagation in the plane (x1t). The results of the other authors are only the particular cases in our work.